FENOMENA KEMISKINAN PADA MASYARAKAT PETANI SAWAH (Studi Kasus Pada Petani Sawah Di Desa Karang Anyar Kec. Jati Agung Kab. Lampung Selatan) - Salim, Agus; Kahono, Gunawan Budi (SOCIOLOGIE, 2013)
This research to determine the root causes of poverty in the farmers fields and to  determine the limiting factor in the rice farmers to overcome poverty. Usefulness of this research is expected to contribute to Karang Anyar Village, Jati Agung District, Lampung Selatan Regency, so that local governments pay attention to rice farmers in the village. On this basis it is discussed in the formulation of the  problem that includes what the root causes of poverty in rice farmers in Karang Anyar Village, Jati Agung District, Lampung Selatan Regency,  and what is the  limiting factor rice farmers in Karang Anyar Village, Jati Agung District, Lampung Selatan Regency in addressing poverty. To achieve these objectives, the researchers used a qualitative approach to basic research and case studies are  the primary data source is through interviews, observation and other techniques.Keywords: Poverty, farmers fields